Reports of past alcohol and drug use following participation in a motivation enhancing intervention: Implications for clinical assessment and program evaluation - Rosengren David B; Beadnell Blair; Nason Mark; Stafford Pamela A; Daugherty Ray (BMC, 2012)
Abstract Background There is significant interest in the value of motivational approaches that enhance participant readiness to change, but less is known about clients' self-reports of problematic behavior when participating in such interventions. Methods We examined whether participants in a motivationally-based intervention for DUI offenders changed their reports of substance use at postintervention (when reporting on the same 30 days that they reported on at preintervention). Specifically, Study 1 (N = 8,387) tested whether participants in PRIME For Life (PFL) changed their reports about baseline substance levels when asked at postintervention versus at preintervention. Study 2 (N = 192) compared changes in self-reported baseline drinking between PFL and intervention as usual (IAU) participants. Results Many participants in Study 1 did not change their reports about how much they used substances during the 30-day period before baseline. Among those who did, the most common change was an increase in reported amounts of baseline drug use, and typical and peak alcohol use. This sample also showed changes in reports of their baseline pattern of high-risk-use (consistent versus occasional). At postintervention, participants who were younger, single, or endorsing more indicators of alcohol dependence were more likely to later report greater frequency of baseline drug use, and greater peak and typical number of baseline drinks. Gender, education, and race were also associated with reporting inconsistency on some behaviors. In Study 2, PFL participants showed greater increases in reports of peak alcohol use compared to IAU, but both conditions showed similar increases for drugs and typical alcohol use. Conclusions In both research and clinical settings, a segment of participants may initially report less substance use than they do when asked later about the same baseline period. These preliminary findings suggest clinicians and researchers may find postintervention evaluations yield reports of greater baseline alcohol or drug use for some people. For some behaviors, this may occur more often in interventions that target client motivation. Future research should attempt to identify which reports - preintervention vs. postintervention - better reflect actual baseline substance use.